Differential Effects of DNA Supercoiling on Chlamydia Early Promoters Correlate with Expression Patterns in Midcycle - Cheng, Eric (American Society for Microbiology, 2012)
Changes in DNA supercoiling levels during the chlamydial developmental cycle have been proposed as a global mechanism to upregulate midcycle genes, but the effects on early genes are not known. We examined the promoters for 10 Chlamydia trachomatis early genes and found that they could be separated into two subsets based on their responses to DNA supercoiling in vitro. Furthermore, the type of supercoiling response correlated with the in vivo expression pattern for each early gene. One subset of seven early genes had promoters that were transcribed in a supercoiling-insensitive manner over the physiologic range of supercoiling levels that have been measured in Chlamydia. In vivo transcripts for these genes were detected at similar levels during early-stage and midstage times. In contrast, a second subset, represented in our study by three early genes, had supercoiling-dependent promoters that were transcribed at higher levels from more-supercoiled templates, which is the response observed for midcycle genes. Genes in this subset were expressed at higher levels at midstage times than at early times in vivo. We propose that this second subset represents a novel class of chlamydial developmental genes with features of both early and midcycle genes. We hypothesize that expression of these supercoiling-dependent early genes is upregulated by increased chlamydial supercoiling levels in midcycle via their supercoiling-responsive promoters in a manner similar to that for midcycle genes. Thus, we propose that DNA supercoiling is utilized in Chlamydia as a general mechanism to regulate genes in the midstage of the developmental cycle and not just midcycle genes.